(3GdeLQhMjf ef GdeMOKjfs - (3CHh MGJe GdHSJj , GHf MHGf,J (B354 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO GdeMehO s
(3BNQgG (B:s
(3BNQ cJGH GdJGQjN hGdeLQhMjf ef GdeMOKjf , hGdMeO ddg Ydi CaVGdg hGdUdGI Ydi eMeO GdfHi GdCei hBdg hUMHg GdWGgQjf s
(3fSNI bjeIs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B129 s
Keywords: (3GdJGQjNs